Corporate Rescue : Key Concept dalam Kepailitan Korporasi - Asra Asra (Jurnal Hukum IUS QUIA IUSTUM, 2015)
The problems discussed in this research are: first, how is the relationship between liquidation concept and the bankruptcy of solvable and viable (prospective) companies in Indonesia? Second, how is the attitude of the Supreme Court towards the bankruptcy of solvable companies in Indonesia? Third, how is the ideal concept of Indonesia’s corporate bankruptcy law in the future? This was a normative research. This research concludes, first, there is a relationship between the bankruptcy of solvable and viable (prospective) companies in the Commercial Court and liquidation concept implemented in Bankruptcy Law. Second, related to the bankruptcy of solvent companies in the Commercial Court, the Supreme Court calls off the adjudication of the Commercial Court according to several considerations, including the fact that the companies are still prospective and deserve an opportunity to continue their business and the bankruptcy proposal cannot be proven in a simple way. Third, the ideal concepts of Indonesia’s bankruptcy law in the future are (i) Separating the bankruptcy of corporate and individual. (ii) Insolvent becomes a standard of corporate bankruptcy. (iii) Implementing the principles of business continuity which becomes a concept of corporate rescue in the norm of Corporate Bankruptcy Law or Limited Liability Company Acts. (iv) There is a stricter regulation of revocation of bankruptcy of companies which no longer own their assets.